Sejarah Kebudayaan: Hasil Budaya Material Dan Non Material Akibat Adanya Pengaruh Islam Di Nusantara - Mustawhisin, Alfain Nur; Nirmala Puji, Rully Putri; Hartono, Wiwin (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2019)
Indonesia is currently a nation with a diversity of cultures, but in this diversity there is an influence given by foreigners even though not entirely. The influence given by foreigners can be learned from the cultural acculturation in Indonesia, like the acculturation of local culture with Hindu-Buddhist culture, and acculturation of local culture with Islamic culture. The focus of this writing is the result of culture due to the influence given by Islam in Nusantara culture, because nowadays Islamic culture affects many customs or all local traditions run by the wider community. This study was conducted using historical methods, namely heuristics to collect data, criticism for sorting data, interpretation to interpret the data that was received, and historiography to incorporate all the necessary data For historical writing, as well as conducting literature study methods, with a series of research methods, researchers found that the Islamic culture has had considerable influence both in the material and non material culture.